1997
DOI: 10.1097/00004714-199708000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine Pharmacokinetics When Coadministered With Paroxetine or Sertraline in Extensive Metabolizers

Abstract: In vitro studies have shown that fluoxetine and paroxetine are more potent inhibitors of cytochrome CYP2D6 than sertraline. The pharmacokinetics of desipramine when coadministered with the selective serotonin reuptake inhibitors (SSRIs) paroxetine and sertraline were studied in 24 healthy male volunteers (CYP2D6 extensive metabolizers). Desipramine (50 mg/day) was administered for 23 days in each phase of the crossover study with a 7-day drug-free period between phases. In addition, subjects were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 19 publications
5
56
0
Order By: Relevance
“…Nonetheless usual doses and plasma levels of paroxetine can produce extensive inhibition of clearance of coadministered drugs that are substrates for CYP2D6 (Brøsen et al, 1993;Alderman et al, 1997;Ö zdemir et al, 1998;Alfaro et al, 1999). Approaches to predicting clinical pharmacokinetic drug interactions based on in vitro data continue to be controversial (Bertz and Granneman, 1997;Ito et al, 1998;von Moltke et al, 1998b;Venkatakrishnan et al, 2001).…”
Section: Paroxetine Inhibition Of Cyp2d6mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless usual doses and plasma levels of paroxetine can produce extensive inhibition of clearance of coadministered drugs that are substrates for CYP2D6 (Brøsen et al, 1993;Alderman et al, 1997;Ö zdemir et al, 1998;Alfaro et al, 1999). Approaches to predicting clinical pharmacokinetic drug interactions based on in vitro data continue to be controversial (Bertz and Granneman, 1997;Ito et al, 1998;von Moltke et al, 1998b;Venkatakrishnan et al, 2001).…”
Section: Paroxetine Inhibition Of Cyp2d6mentioning
confidence: 99%
“…We previously observed that the in vitro K i for paroxetine versus desipramine hydroxylation yielded an underestimate of the degree of desipramine clearance inhibition when desipramine was coadministered with paroxetine in a clinical study (von Moltke et al, 1995;Alderman et al, 1997). We accounted for this discrepancy on the basis of extensive partitioning of paroxetine from plasma into hepatic tissues such that intrahepatic concentrations substantially exceeded total plasma concentrations (von Moltke et al, 1995).…”
mentioning
confidence: 99%
“…2 for the interaction of paroxetine with desipramine (Alderman et al, 1997). For purposes of this exercise, the steady-state pharmacokinetic profile of desipramine (50 mg q.d.)…”
Section: In Vitro-in Vivo Extrapolation Of Paroxetine Ddimentioning
confidence: 99%
“…Examples of characterized clinical interactions with paroxetine include its effects on the kinetics of desipramine (Brøsen et al, 1993;Alderman et al, 1997), perphenazine (Ö zdemir et al, 1997), metoprolol (Hemeryck et al, 2000), risperidone (Spina et al, 2001), and atomoxetine (Belle et al, 2002), where the clearance of the victim drugs is impaired by 5-to 8-fold. In addition, paroxetine displays nonlinear accumulation kinetics with steady-state exposures exceeding projections from single-dose kinetics by ϳ5-fold in CYP2D6 extensive metabolizers but not in CYP2D6 poor metabolizers (Kaye et al, 1989;Sindrup et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…An approximately 10-fold increase in the C max and AUC 24 of paroxetine and an approximately 2-fold increase in these parameters for sertraline occurred simultaneously with the desipramine concentration changes. Thus, when co-administered with 50 mg/day desipramine, sertraline had significantly less pharmacokinetic interaction than paroxetine with desipramine at the recommended starting dosages of 50 mg/day and 20 mg/day, respectively, as initially reported by Alderman et al, [81].…”
Section: Pharmacogenomics Of Antidepressantsmentioning
confidence: 57%